Determinación de la capacidad antioxidante in vitro de cuatro variedades de fréjol (Phaseolus vulgaris L.) - Molina Penagos, Melanie Dayanna (2024)
The purpose of this research entitled: “Determination of the in vitro antioxidant capacity of four varieties of beans (Phaseolus Vulgaris L.)” was the evaluation of four varieties of beans in order to select the best treatment. Common beans (Phaseolus vulgaris L.) correspond to the third most important dietary legume; it is a traditional crop that is part of the basic diet as it is a high source of low-cost protein. It is worth mentioning that in Ecuador the area planted with beans had grown by approximately 6%, in turn in the province of Bolívar in the Guaranda canton it has high planting levels of 10% to 50% in its great variety of beans, however , bean production is mostly intended for direct human consumption. Even so, its study is limited, that is, it does not include an analysis of the nutritional and functional properties of the varieties that grow in the area. Therefore, an opportunity has been created to carry out an analysis of the different varieties of beans, since they present different characteristics, such as physical characteristics of their grains, size, hardness and moisture content, including establishing an analysis of antioxidant activity. In such a way that the results obtained from the analyzes carried out on treatments T3 (Brown Bean + Acetonitrile) and T12 (UEB-Bombolín Bean + Acetonitrile) were better in the polyphenol content. In the case of flavonoids, the treatments T8 (Panamita Bean + Ethanol) and T2 (Brown Bean + Ethanol) stood out, and in anthocyanins the highest treatment was T6 (Black Bean + Acetonitrile). The results reveal that the brown bean variety demonstrated to have antioxidant properties, highlighting a quantification of 73.49 μmol ET/g sample. As a consequence of this research, it was decided to carry out an additional experiment to take advantage of the outstanding properties of the brown bean variety, thus creating a protein supplement, in which the content was 70.81% protein, consolidating the position of the variety of brown beans as a main vegetable protein option. This study provides a solid foundation for future research in the field of food and nutrition, opening the doors to new possibilities to improve health through the incorporation of foods with exceptional antioxidant properties, such as the variety of brown beans.